Fast profiling of protease specificity reveals similar substrate specificities for cathepsins K, L and S. Issue 14 (9th March 2015) - Vizovišek, Matej; Vidmar, Robert; Van Quickelberghe, Emmy; Impens, Francis; Andjelković, Uroš; Sobotič, Barbara; Stoka, Veronika; Gevaert, Kris; Turk, Boris; Fonović, Marko; Van Damme, Petra; Gevaert, Kris
<x xml:space="preserve">Abstract</x> Proteases are important effectors of numerous physiological and pathological processes. Reliable determination of a protease's specificity is crucial to understand protease function and to develop activity‐based probes and inhibitors. During the last decade, various proteomic approaches for profiling protease substrate specificities were reported. Although most of these approaches can identify up to thousands of substrate cleavage events in a single experiment, they are often time consuming and methodologically challenging as some of these approaches require rather complex sample preparation procedures. For such reasons their application is often limited to those labs that initially introduced them. Here, we report on a fast and simple approach for proteomic profiling of protease specificities (fast profiling of protease specificity (FPPS)), which can be applied to complex protein mixtures. FPPS is based on trideutero‐acetylation of novel N‐termini generated by the action of proteases and subsequent peptide fractionation on Stage Tips containing ion‐exchange and reverse phase chromatographic resins. FPPS can be performed in 2 days and does not require extensive fractionation steps. Using this approach, we have determined the specificity profiles of the cysteine cathepsins K, L and S. We further validated our method by comparing the results with the specificity profiles obtained by the N‐terminal combined fractional diagonal chromatography method. This comparison pointed to almost identical substrate specificities for all three cathepsins and confirmed the reliability of the FPPS approach. All MS data have been deposited in the ProteomeXchange with identifiers PXD001536 and PXD001553 (http://proteomecentral.proteomexchange.org/dataset/PXD001536; http://proteomecentral.proteomexchange.org/dataset/PXD001553).